Combined solid‐phase microextraction and high‐performance liquid chromatography with ultroviolet detection for simultaneous analysis of clenbuterol, salbutamol and ractopamine in pig samples. (11th July 2013) - Du, Wei; Zhang, Siruo; Fu, Qiang; Zhao, Gang; Chang, Chun
ABSTRACT: A simple and sensitive method based on the combination of solid‐phase microextraction (SPME) and high‐performance liquid chromatography with ultroviolet detection was developed for the simultaneous determination of clenbuterol, salbutamol and ractopamine in pig samples. Parameters of the SPME procedure affecting extraction efficiency, such as the type of fiber, extraction time, extraction temperature, ion strength, pH of sample and stirring rate, were optimized. The developed method was validated according to the International Conference on Harmonization guidelines. The calibration curves were linear over a range of 0.5–50 µg/L for clenbuterol and ractopamine, and 0.2–20 µg/L for salbutamol. The limits of detection were 0.1 µg/L for clenbuterol, 0.05 µg/L for salbutamol and 0.1μg/L for ractopamine, respectively. The averages of intra‐ and inter‐day accuracy ranged from 79.8 to 92.4%. The intra‐day and inter‐day precision were below 9.6% for the three analytes. This method exhibited the advantages of simplicity, rapidity and low solvent consumption, and was suitable for the monitoring of β 2 ‐agonists residue in pig samples. Copyright © 2013 John Wiley & Sons, Ltd.